Pendidikan Sebagai Agen Perubahan Dalam Mengembangkan Budaya Keadilan Sosial - Salwa Andini; Yakobus Ndona (Pusat Riset dan Inovasi Nasional, 2024)
Education has an important role as an agent of change in developing a culture of social justice. This article analyzes how the education system can be an effective instrument for promoting equality, inclusivity and justice in society. Through a critical pedagogical approach and a curriculum based on social justice values, education can form individuals who are aware of the importance of human rights and justice. This study also explores the challenges and opportunities faced by educational institutions in implementing the concept of social justice, as well as providing strategic recommendations for maximizing the role of education in creating a more just and equal society.